Blockchain Foundations and Applications - Yi, Xun.; Yang, Xuechao; Kelarev, Andrei; Lam, Kwok Yan.; Tari, Zahir (Cham : Springer International Publishing : Imprint: Springer, 2022)
This monograph provides a comprehensive and rigorous exposition of the basic concepts and most important modern research results concerning blockchain and its applications. The book includes the required cryptographic fundamentals underpinning the blockchain technology, since understanding of the concepts of cryptography involved in the design of blockchain is necessary for mastering the security guarantees furnished by blockchain. It also contains an introduction to cryptographic primitives, and separate chapters on bitcoin, ethereum and smart contracts, public blockchain, private blockchain, cryptocurrencies, and blockchain applications. This volume is of great interest to active researchers who are keen to develop novel applications of blockchain in the field of their investigatio. Further, it is also beneficial for industry practitioners as well as undergraduate students in computing and information technology.
Chapter 1. Cryptographic Primitives -- Chapter 2. Distributed Consensus -- Chapter 3. Bitcoin, Ethereum and Smart Contracts -- Chapter 4. Cryptocurrencies -- Chapter 5. Blockchain Types and Deployment Models -- Chapter 6. Blockchain Applications in Supply Chain -- Chapter 7. Blockchain Applications in Health Care -- Chapter 8. Blockchain Applications in Manufacturing -- Chapter 9. Conclusion.
Keywords: Blockchains (Databases).; Computer science-Mathematics.; Electronic commerce; Engineering mathematics; Engineering-Data processing; Medical informatics; Blockchain; Mathematics of Computing; e-Commerce and e-Business.; Mathematical and Computational Engineering Applications; Health Informatics